Electrochemical engineering : science and technology in chemical and other industries - Wendt, Hartmut (Springer, 1999)
1- The scope and history of electrochemical engineering. 2- Basic principles and laws electrochemistry. 3- Electrochemical thermodynamics. 4- Electrode kinetics and electrocatalysis. 5- Mass transfer by fluid flow, convective diffusion and ionic electricity. 6- Electrochemical reaction engineering. 7- Electrochemical engineering of porous electrodes and disperse. 8- Electrochemical cell and plant engineering. 9- Process development. 10- Industrial electrodes. 11- Industrial processes. 12- Fuel cells.